Identifying Toll-like Receptor Expression in Cutaneous Sarcoidosis. (January 2015) - Huizenga, Taryn; Kado, Jessica; Mehregan, Darius R.; Diamond, Stephanie
Abstract : Abstract: Toll-like receptors (TLRs) are known to be expressed in the skin. Antigenic stimulation of TLRs in the skin has been implicated in several inflammatory dermatologic diseases including psoriasis, syphilis, atopic dermatitis, and cutaneous T-cell lymphoma. However, the expression of TLRs in cutaneous sarcoidosis has not yet been defined. Expression of TLRs 1–9 was examined in cutaneous sarcoid by immunohistochemical staining. It was found that TLRs 5 and 6 stained most intensely in both the granulomas and epidermis of the sarcoid cases. TLRs 2, 3, 4, 7, and 8 stained more intensely compared with normal skin. All sarcoidosis cases showed an increased level of staining compared with the control. The nuclear factor-kappa B activation pathway was confirmed by staining for p65. All cases strongly stained for p65 in the granulomas and varied in staining intensity in the epidermis. The identified TLR expression in cutaneous sarcoidosis indicates that a bacterial antigen could be an etiologic agent of the disease. Future studies that clearly define the etiology of sarcoid will lead to better therapies and a better prognosis for affected patients.